INSTITUTIONAL ENVIRONMENT OF PUBLIC FINANCE (INNOVATIVE ECONOMY, 2021)
Derlytsia A.Yu. INSTITUTIONAL ENVIRONMENT OF PUBLIC FINANCEPurpose. The aim of the article is research of the institutional environment of public finance and its components in the light of achievements of foreign and domestic economic science.Methodology of research. The following general and special methods are used to achieve this goal: comparative analysis – in assessing alternative approaches to the interpretation of the concept of institution; method of scientific abstraction – in highlighting the essential features of financial institutions and their differences from fiscal institutions; systemic, structural analysis, grouping – in identifying the components of the institutional environment of public finance and structural features of the public sector. Findings. Alternative approaches of institutional theory to the interpretation of the concept of institution are considered. A compromise application the interpretation of institutions in the approaches of D. North and O. Williamson to the sphere of public finance has been made. The components of the institutional environment of public finance are distinguished: institutions (norms, rules), institutional units (organizations, structures), transactions (interaction, relations). The institutional structure of the public sector is considered. The principle of “presumption of inefficiency” as a key one in the institutional analysis of the sphere of public finance is outlined.Originality. The paper substantiates the components of the institutional environment of public finance by clearly outlining the semantic use of the terms “institution” and “institutions” in relation to this area.Practical value. The approaches to the interpretation of the concepts “financial institutions”, “institutional environment”, “public sector” proposed in the research, will contribute to the development of a unified approach in the domestic institutional theory.Key words: public finance, financial institutions, fiscal institutions, institutional environment, institutional units, public sector, transactions.
Keywords: Key words; public finance; financial institutions; fiscal institutions; institutional environment; institutional units; public sector; transactions.